PELATIHAN BAGI UMKM MENUJU UMKM NAIK KELAS DI PANTAI KUTA LOMBOK TENGAH - Syahrul, Syahrul; Apriyansyah, Roli (LPPM Institut Pendidikan Nusantara Global, 2024)
The community service to be carried out by our Team is located in the Labuapi District. The district consists of 4 villages including Kota Sari Village, Labuapi Village, Rawa Arum Village, and Gerem Village. Not a few people in Kuta Beach Central Lombok work as entrepreneurs, especially MSME entrepreneurs such as processed food, workshop operators, snack & catering businesses, and others. There are MSME business actors who are still pioneering business activities, but there are also business actors who have been doing business for a long time but their businesses have not been able to develop well. Based on surveys conducted in the field, it is shown that the high level of business activities carried out by business actors has not been accompanied by an understanding of the supporting factors in conducting business activities such as simple bookkeeping so business actors only focus on profits without paying attention to business supporting factors. Based on this illustration, MSME entrepreneurs need an understanding of simple bookkeeping to support business activities so that they can develop well in the future.